Influence of p16 status on indication and outcome of salvage neck dissection in oropharyngeal cancer. (1st February 2021) - Mueller, Sarina Katrin; Mantsopoulos, Konstantinos; Semrau, Sabine; Agaimy, Abbas; Eckstein, Markus; Traxdorf, Maximilian; Gostian, Antoniu Oreste; Goncalves, Miguel; Sievert, Matti; Haderlein, Marlen; Grundtner, Philipp; Hecht, Markus; et al.
Abstract: Background: Human papillomavirus (HPV)+ and HPV– oropharyngeal squamous cell carcinomas (OPSCC) are separate tumor entities. Aims/Objectives: The aim of this study was to examine if the p16 status influences the need and outcome of a salvage neck dissection (SND) after primary radiochemotherapy (pRCT). Material and methods: Retrospective study of 164 patients ( n  = 108 p16–, n  = 56 p16+) who underwent pRCT for OPSCC between 2009 and 2016. HPV status was defined via p16 immunohistochemical staining. Clinical nodal status was assessed using ultrasound and computed tomography of the neck with contrast. Results: Of the 56 p16+ patients, 17 (30.4%) patients were given an indication for a SND after pRCT with 4 (23.5%) patients showing persistent malignant nodes. Of the 108 p16– patients, 24 (22.2%) patients underwent a SND with 8 (33.3%) patients showing persistent malignant nodes. There was no significant association of the p16 status and neither the indication for SND (p(Chi 2 (two-sided)-Test) = 0.25, ϕ = 0.34) nor the occurrence of positive nodes (p(Chi 2 (two-sided)-Test) = 0.74, ϕ = 0.50). The probability for persistence of the ypN + nodal status independent of HPV-status was 29.2%(12/41). Conclusions and significance: There was neither a significant association between the p16 status and the indication for a SND nor for persistent malignant nodal disease after pRCT.